Halogen Bonding in Haspin-Halogenated Tubercidin Complexes: Molecular Dynamics and Quantum Chemical Calculations - Yujing Zhou; Ming Wah Wong (Molecules, 2022)
Haspin, an atypical serine/threonine protein kinase, is a potential target for cancer therapy. 5-iodotubercidin (5-iTU), an adenosine derivative, has been identified as a potent Haspin inhibitor in vitro. In this paper, quantum chemical calculations and molecular dynamics (MD) simulations were employed to identify and quantitatively confirm the presence of halogen bonding (XB), specifically halogen∙∙∙π (aromatic) interaction between halogenated tubercidin ligands with Haspin. Consistent with previous theoretical finding, the site specificity of the XB binding over the ortho-carbon is identified in all cases. A systematic increase of the interaction energy down Group 17, based on both quantum chemical and MD results, supports the important role of halogen bonding in this series of inhibitors. The observed trend is consistent with the experimental observation of the trend of activity within the halogenated tubercidin ligands (F < Cl < Br < I). Furthermore, non-covalent interaction (NCI) plots show that cooperative non-covalent interactions, namely, hydrogen and halogen bonds, contribute to the binding of tubercidin ligands toward Haspin. The understanding of the role of halogen bonding interaction in the ligand–protein complexes may shed light on rational design of potent ligands in the future.